Er,Cr:YSGG Laser assisted Removal of Ceramic Veneers Cemented with G-Cem Resin Cement:(An in vitro study) - Bydaa A. Abood; Abduladheem Raouf Sulaiman (University of Mosul, College of Dentistry, 2023)
Aims: To evaluate the efficiency of Er,Cr: YSGG laser in debonding of veneers made of lithium disilicate (E-max®) as measured with the shear bond strength(SBS), determine the impact of two laser powers on the SBS required to debond veneers, and finally determining the mode of failure for each group. Materials and methods: Thirty ceramic discs (1mm in thickness and 5mm in diameter) were prepared according to the manufacturer's instructions. The facial surfaces of enamel for thirty bovine teeth were prepared smooth and the discs cemented onto these prepared surfaces by using GCem™ veneer light cure adhesive cement. Specimens were stored in distilled water for 48hours, after which they were divided randomly into three equal groups (n=10) according to the laser power used as follows: Cont.: Control group that wasn't subjected to laser irradiation; L3: Group irradiated at 3 watt (60 sec.); L5: Group irradiated at 5 watt (60 sec.). SBS was measured by "Instron universal testing machine" and the mode of failure was assessed using stereomicroscope. Results: Both laser irradiated groups showed significant difference in reducing the SBS (p=.000), some of discs debonded during laser irradiation. However, there was no significant difference between the two laser powers used (p=.418). Conclusions: Er, Cr: YSGG could be a safe, effective, fast, and harmless method for reducing SBS of bonded E-max® laminate veneers, without affecting the tooth and the veneer itself. Since there was no significant difference between the two laser powers used, it is advocated to use 3 watts.